Recent Advances of L-ornithine Biosynthesis in Metabolically Engineered Corynebacterium glutamicum - Wu, Xiao-Yu; Guo, Xiao-Yan; Zhang, Bin; Jiang, Yan; Ye, Bang-Ce (Frontiers in Bioengineering and Biotechnology, 2020)
Abstract: L-ornithine, a valuable non-protein amino acid, has a wide range of applications in the pharmaceutical and food industries. Currently, microbial fermentation is a promising, sustainable, and environment-friendly method to produce L-ornithine. However, the industrial production capacity of L-ornithine by microbial fermentation is low and rarely meets the market demands. Various strategies have been employed to improve the L-ornithine production titers in the model strain, Corynebacterium glutamicum, which serves as a major indicator for improving the cost-effectiveness of L-ornithine production by microbial fermentation. This review focuses on the development of high L-ornithine-producing strains by metabolic engineering and reviews the recent advances in breeding strategies, such as reducing by-product formation, improving the supplementation of precursor glutamate, releasing negative regulation and negative feedback inhibition, increasing the supply of intracellular cofactors, modulating the central metabolic pathway, enhancing the transport system, and adaptive evolution for improving L-ornithine production.